2023
DOI: 10.1080/15592324.2023.2245625
|View full text |Cite
|
Sign up to set email alerts
|

Seedling growth and photosynthetic response of Pterocarpus indicus L. to shading stress

Abstract: In tropical forests, the shade provided by tree canopies and extreme climate causes inhibition of plant seedling growth due to the lack of light. However, the plants can acclimate to such environmental stress by generating specific responses. The present study aimed to investigate the effects of shading conditions on ecophysiological performance of Narra seedlings ( Pterocarpus indicus L.) via a mesocosm experiment. A pot experiment was conducted for 20 weeks in a greenhouse with differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 91 publications
0
1
0
Order By: Relevance
“…According to our previous analysis of C. fusca CHK0059 cell composition, it contained high levels of N (91.2 g kg −1 ), P (9.38 g kg −1 ), K (2.62 g kg −1 ), Ca (1.05 g kg −1 ), Mg (5.85 mg kg −1 ), etc., inferring that added Chlorella is likely to be well absorbed as a nutrient source for strawberry plants. In addition, the improved nutritional status of the plants appeared to positively influence the photosynthetic capacity by regulating their morphological characteristics, such as specific leaf area and leaf mass ratio, that are highly related to the efficiencies of light capture and carbon gain [ 32 , 33 ]. A similar research result has also been reported by Kim et al [ 26 ], who demonstrated significant increases in shoot height, leaf thickness, and leaf pigments of the strawberry cultivar ‘Seolhyang’ by C. fusca CHK0059 application.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous analysis of C. fusca CHK0059 cell composition, it contained high levels of N (91.2 g kg −1 ), P (9.38 g kg −1 ), K (2.62 g kg −1 ), Ca (1.05 g kg −1 ), Mg (5.85 mg kg −1 ), etc., inferring that added Chlorella is likely to be well absorbed as a nutrient source for strawberry plants. In addition, the improved nutritional status of the plants appeared to positively influence the photosynthetic capacity by regulating their morphological characteristics, such as specific leaf area and leaf mass ratio, that are highly related to the efficiencies of light capture and carbon gain [ 32 , 33 ]. A similar research result has also been reported by Kim et al [ 26 ], who demonstrated significant increases in shoot height, leaf thickness, and leaf pigments of the strawberry cultivar ‘Seolhyang’ by C. fusca CHK0059 application.…”
Section: Discussionmentioning
confidence: 99%